Brown adipose tissue is involved in diet-induced thermogenesis and whole-body fat utilization in healthy humans - Hibi, M; Oishi, S; Matsushita, M; Yoneshiro, T; Yamaguchi, T; Usui, C; Yasunaga, K; Katsuragi, Y; Kubota, K; Tanaka, S; Saito, M (International Journal of Obesity, 2016)
Background/Objectives: Brown adipose tissue (BAT) is a potential therapeutic target against obesity and diabetes through thermogenesis and substrate disposal with cold exposure. The role of BAT in energy metabolism under thermoneutral conditions, however, remains controversial. We assessed the contribution of BAT to energy expenditure (EE), particularly diet-induced thermogenesis (DIT), and substrate utilization in human adults. Methods: In this cross-sectional study, BAT activity was evaluated in 21 men using 18 F-fluoro-2-deoxy- D -glucose positron emission tomography combined with computed tomography ( 18 F-FDG-PET/CT) after cold exposure (19 °C). The subjects were divided into BAT-positive ( n= 13) and BAT-negative ( n= 8) groups according to the 18 F-FDG-PET/CT findings. Twenty-four hour EE, DIT and respiratory quotient were measured using a whole-room indirect calorimeter at 27 °C. Results: Body composition, blood metabolites and 24-h EE did not differ between groups. DIT (%), calculated as DIT divided by total energy intake, however, was significantly higher in the BAT-positive group (BAT-positive: 9.7±2.5%, BAT-negative: 6.5±4.0%, P =0.03). The 24-h respiratory quotient was significantly lower ( P =0.03) in the BAT-positive group (0.861±0.027) than in the BAT-negative group (0.889±0.024). Conclusion: DIT and fat utilization were higher in BAT-positive subjects compared to BAT-negative subjects, suggesting that BAT has a physiologic role in energy metabolism.